Peran Screencast dalam Memfasilitasi Pembelajaran - Yerry Soepriyanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
Screencast or screencasting is a term related to videos that capture the content displayed on a computer monitor. The purpose of this article is to provide an explanation and discussion about the history behind these two terms and their roles in facilitating learning. The discussion also includes previous studies conducted to provide evidence of the role of screencasts in supporting the learning process. The sources referenced include articles or documentation published in reputable journals, magazines, and trustworthy websites between 2004 and 2018.